ECB Announcements and Stock Market Volatility - Frederik Neugebauer (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
This paper documents that ECB announcements increase the stock market volatility in the euro area (EA) on the same day. I consider two volatility measures from January 1998 to May 2019. First, a realized volatility measure uses intraday data for 8 different stock market indices. Second, a range measure approximates volatility using daily prices from 11 national stock market indices. Employing event study methods I find a stronger impact following the global financial crisis starting in 2007. All assets react similarly so that no national peculiarities arise. The effects also spill over to 7 non-EA markets analyzed.
Keywords: E52; E58; G12; G14; 330; ECB announcements; asset price volatility; event study